Contribution of thermogenic organic matter to the formation of biogenic gas hydrate: Evidence from geochemical and microbial characteristics of hydrate-containing sediments in the Taixinan Basin, South China Sea. (February 2017) - Gong, Junli; Sun, Xiaoming; Xu, Li; Lu, Hongfeng
Abstract: High-saturation (40–100%), microbial gas hydrates have been acquired by expedition GMGS2 from the Taixinan Basin. In this study, geochemical and microbial features of hydrate-containing sediments from the drilling cores (GMGS2-09 and GMGS2-16) were characterized to explore their relationships with gas hydrate formation. Results showed that the average TOC content of GMGS2-09 and GMGS2-16 were 0.45% and 0.63%, respectively. They could meet the threshold for in situ gas hydrate formation, but were not available for the formation of high-saturation gas hydrates. The dominant members of Bacteria at the class taxonomic level were Alphaproteobacteria, Bacilli, Bacteroidia, Epsilonproteobacteria and Gammaproteobacteria, and those in Archaea were Marine_Benthic_Group_B (MBGB), Miscellaneous_Crenarchaeotic_Group (MCG), Group C3, Methanomicrobia and Methanobacteria. Indicators of microbes associated with thermogenic organic matter were measured. These include: (1) most of the dominant microbes had been found dominant in other gas hydrates bearing sediments, mud volcanos as well as oil/coal deposits; (2) hydrogenotrophic methanogens and an oilfield-origin thermophilic, methylotrophic methanogen were found dominant the methanogen community; (3) hydrocarbon-assimilating bacteria and other hyperthermophiles were frequently detected. Therefore, thermogenic signatures were inferred existed in the sediments. This deduction is consistent with the interpretation from the seismic reflection profiles. Owing to the inconsistency between low TOC content and gas hydrates with high saturation, secondary microbial methane generated from the bioconversion of thermogenic organic matters (oil or coal) was speculated to serve as enhanced gas flux for the formation of high-saturation gas hydrates. A preliminary formation model of high-saturation biogenic gas hydrates was proposed, in which diagenesis processes, tectonic movements and microbial activities were all emphasized regarding to their contribution to gas hydrates formation. In short, this research helps explain how microbial act and what kind of organic matter they use in forming biogenic gas hydrates with high saturations. Graphical abstract: Highlights: The geochemical and microbial characteristics of gas hydrate-containing sediments from the Taixinan Basin were analyzed. TOC content meets the threshold for situ gas hydrate formation but cannot form high saturated gas hydrates. Indicators of microbes associated with thermogenic organic matters were measured. Secondary biogenic methane was inferred in forming high-saturation biogenic hydrates.